Spatial and seasonal analysis of antimicrobials and toxicity tests with Daphnia magna, on the sub-basin of Piracicaba river, SP, Brazil - Torres, Nádia Hortense; de Salles Pupo, Marilia Moura; Ferreira, Luiz Fernando Romanholo; Maranho, Lucineide Aparecida; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Vilca, Franz Zirena; de Hollanda, Luciana Maria; Tornisielo, Valdemar Luiz (Elsevier, 2017)
Antimicrobials are pharmaceuticals considered micropollutants because they are found in wastewaters at low concentrations (ng L−1), which is the case of Enrofloxacin (ENR), Erythromycin (ERY), Norfloxacin (NOR) and Ciprofloxacin (CIP). These compounds are used to treat respiratory, urinary, sexually transmitted diseases, and skin infections being excreted by the body. Due to their composition they are considered of high risk to flora and fauna. The goal of this work was to determine possible concentration of Enrofloxacin, Erythromycin, Norfloxacin and Ciprofloxacin in water, after methodology validation to analyze and monitor the antimicrobials in superficial water and urban supply. Thus, liquid chromatography coupled with mass spectrometer with electrospray ionization source (LC-ESI–MS/MS) was used. The results obtained showed limit of detection (LOD) varying from 0.1 to 0.8 ng L−1; linearity was obtained in the gap between 10 and 200 ng L−1 for Erythromycin, and 40–200 ng L−1 for Ciprofloxacin, Norfloxacin and Enrofloxacin. Regression coefficients (r2) were over 0.9 and recovery rates were between 82 and 118% of the samples spiked with 50 and 100 ng L−1. This validated methodology was successfully used to determine antimicrobials level in water samples collected along Piracicaba River and treated water samples of Piracicaba city. From these samples, the antimicrobial mostly found was Norfloxacin in concentrations varying from 8 to 18 ng L−1 in samples collected in dry seasons, whereas Ciprofloxacin, Enrofloxacin and Erythromycin were not found in any of the samples collected. For the 48 h acute tests with Daphnia magna, Norfloxacin and Erythromycin were considered as “low toxicity”, while other compounds did not present any toxicity effect.
Keywords: Aquatic environment; Environmental contamination; Mass spectrometer; Superficial water